Understanding Differences in Food Distribution Methods Among Food Pantries in Baltimore City, MD (P04-037-19). (13th June 2019) - Craig, Hope; Yan, Sally; Gunen, Bengucan; Adams, Lindsay; Ali, Shahmir; Gu, Yuxuan; Poirier, Lisa; Gittelsohn, Joel
Abstract: Objectives: Food pantries are increasingly being used to address long-term hunger in food insecure households in the United States. The client choice food distribution model is considered best practice, but there is lack of agreement in the literature about what this means. This study aims to explore the nuances of food distribution methods considered client choice at food pantries in Baltimore City, MD. Methods: In-depth interviews (IDIs) were conducted with 22 randomly selected food pantry managers in Baltimore City to explore food distribution and pantry management. Three Food Pantry Environment Checklists were also conducted, approximately 1 month apart, at each pantry to collect further information on pantry operations and inventory. IDIs were audio-recorded and transcribed. Data were analyzed thematically to identify patterns in how food is distributed and managers' experiences with the client choice model. Results: Most managers reported using a combination of distribution methods, including client choice in which clients shop directly from pantry selves (14/22), assisted bagging in which staff help clients bag items according to client requests (21/22), and pre-packaged distribution in which clients receive standard pre-packed bags (16/22). Though many managers used client choice, only 10 said clients pick up and bag their own items. Most managers said clients are guided by pantry staff and are limited in their food selection based on food category and supply. Several managers reported client choice helps reduce food waste and accommodates clients' food preferences; however, some had concerns about lack of resources (budget, time, and food supply) for this approach. Several pantries with pre-packaged distribution incorporated client choice by stocking products based on clients' preferences and allowing clients to swap out items. Conclusions: Food limits associated with different food distribution methods may impact the healthiness of products that clients receive. Improving access to healthy foods at pantries requires concerted efforts that address the multiple methods of distributing food. Evidence-based recommendations are needed to strengthen the client choice model and create engaging, dignified spaces that make healthy food choices both feasible and acceptable at pantries. Funding Sources: Johns Hopkins Bloomberg American Health Initiative, Johns Hopkins Urban Health Institute.